2014
DOI: 10.1093/mnras/stu1502
|View full text |Cite
|
Sign up to set email alerts
|

A variable P舁v broad absorption line and quasar outflow energetics

Abstract: Broad absorption lines (BALs) in quasar spectra identify high velocity outflows that might exist in all quasars and could play a major role in feedback to galaxy evolution. The viability of BAL outflows as a feedback mechanism depends on their kinetic energies, as derived from the outflow velocities, column densities, and distances from the central quasar. We estimate these quantities for the quasar, Q1413+1143 (redshift z e = 2.56), aided by the first detection of P v λ1118, 1128 BAL variability in a quasar. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 54 publications
(134 reference statements)
5
72
0
2
Order By: Relevance
“…One explaining the variability as caused by rapid crossing of an absorbing cloud, and one as a rapid change of ionization in the ionized material (e.g., Lundgren et al 2007;Filiz Ak et al 2012;Capellupo et al 2013;Wildy & Goad 2015;Grier et al 2015). Recently, Capellupo et al (2014) carried out a detailed study of the variability of the A1-A2 absorbers in H1413+117.…”
Section: Differences Of Light Paths Between Imagesmentioning
confidence: 99%
“…One explaining the variability as caused by rapid crossing of an absorbing cloud, and one as a rapid change of ionization in the ionized material (e.g., Lundgren et al 2007;Filiz Ak et al 2012;Capellupo et al 2013;Wildy & Goad 2015;Grier et al 2015). Recently, Capellupo et al (2014) carried out a detailed study of the variability of the A1-A2 absorbers in H1413+117.…”
Section: Differences Of Light Paths Between Imagesmentioning
confidence: 99%
“…In contrast, Wildy et al (2014) claimed that BAL variations were not correlated with continuum variations, casting doubt on this interpretation. In addition, Capellupo et al (2014) found variable P V absorption lines associated with non-black C IV absorption lines, which they interpreted as ionized gas moving across the continuum source. There is also an argument that the ionizing continuum may vary in a different way from the observed UV continuum due to changes in a presumed high ionization shielding gas (Filiz Ak et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The numbers are small, but it does indicate that BALQSOs are at least as likely to be FIR-luminous as nonBALQSOs, and possibly even more likely, in contrast to the result from Cao Orjales et al (2012). In special circumstances, the distance to the absorbing material, and thus the mass of the material and energy of the outflow, can be estimated, and it is found that the energy contained within the outflow is sufficient to have an effect on galaxy scales (Moe et al 2009, Capellupo, Hamann, & Barlow 2014. The outflows with distance estimates put the absorbing material at kiloparsec-scale distances, far beyond the immediate black hole neighbourhood, consistent with the radial extent found within simulations.…”
Section: Discussionmentioning
confidence: 98%
“…Similar outflows can also be observed in X-rays (Reeves, O'Brien, & Ward 2003, Reeves et al 2009). The energy injected, and ultimately the effect on the BALQSO host galaxy, is difficult to determine, except under special circumstances (Moe et al 2009, Dunn et al 2010, Capellupo, Hamann, & Barlow 2014.…”
Section: Introductionmentioning
confidence: 99%